(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents new information about the distribution of coccinellids and some bioecological features. Coccinellid beetles have been classified into phytophagous and carnivorous coccinellid beetles based on their habitat and feeding spectrum. Phytophages, in turn, were grouped into small groups, such as phyllophage, anthophage, and mithetophage. Predatory coccinellid beetles are also divided into groups of aphidophages, mixoentomophages and acarifages.